EC agricultural reform policy—The beginning of a new form of protectionism? - Monika Hartmann; Peter Michael Schmitz (Intereconomics, 1988)
The European Community regards its current agricultural policy “reforms” as an adjustment to the reality of the market and hence as a contribution to easing the strains in world agricultural trade and reducing worldwide distortions in resource allocation. A detailed analysis gives ground for scepticism.
Keywords: 330; European Community